Are Financial Ratios Universal? A Cross-Country Perspective - Dian Indrianto; Dwi Dewianawati; Erry Setiawan; Buyung Cahya Perdana; Adhis Helsa Aurellia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the efficiency of financial ratios in assessing corporate performance across countries. Although financial ratios are widely used as concise indicators of profitability, liquidity, solvency, and market value, their interpretive accuracy may vary across institutional, regulatory, financial, and macroeconomic environments. The objective of this study is to conceptually evaluate whether financial ratios can function as universally comparable performance measures in heterogeneous cross-country settings. Using a qualitative literature-based method, this study synthesizes prior findings on financial ratio analysis, financial statement comparability, market efficiency, regulatory enforcement, and macroeconomic stability. The findings indicate that profitability, liquidity, solvency, and market-based ratios are context-dependent indicators rather than universally stable measures. Their efficiency is influenced by accounting standards, audit quality, leverage norms, tax systems, capital market maturity, and macroeconomic volatility. The study proposes a contextual framework for interpreting financial ratios according to their sensitivity to national conditions. The implication is that researchers, analysts, and investors should combine ratio analysis with institutional and macroeconomic diagnostics to reduce biased performance interpretation in cross-country corporate evaluation.